Developing of Interactive Game Based on Role Play Game to Improve the Reading Abilities - Rakimahwati, Rakimahwati; Roza, Desmawati (Universitas Negeri Semarang, 2020)
The ability to read is the most important thing for children's intellectual development. One of the efforts is application of interactive form games. Games can improve children's reading skills because they match concept of children's learning while playing. This study aims to develop interactive RPG-based games to improve children's reading skills. The method used is ADDIE. The steps taken after the product is made are validity test, practicality test and effectiveness test. The stages after the product are made are validity test, practicality test and effectiveness test. The results of the validity of the game were 94.5% (very valid category), and 94% practicality (very practical category). In terms of effectiveness, this game was proven to be able to improve children's reading skills, namely 91%. Emphasis on the reading aspect includes the ability to read pictures, say each letter in 1 word, read words, find same vowels and letters. Based on 5 items, effectiveness shows a strong relationship between aspects of image recognition, reading words, finding the same letters to improve children's reading skills using interactive RPG games. Two other items are inferior, namely mentioning each letter in one word and vowels because game does not guide specifically like other aspects. This game is useful in increasing reading literacy, counting through interactive games so that children will be happy in the learning process, besides that it can hone children's visual and kinesthetic intelligence.